Análisis de la Política Pública de Atracción a la Inversión Extranjera Directa en Ecuador, periodo 2018-2022. - Briceño Ruiz, Edgar Paúl (2024)
Public policies are planned and developed to solve common problems and needs that affect society. In this case, this research analyzed the public policy of the Ecuadorian State to attract Foreign Direct Investment (FDI) in the period 2018-2022, understood as an international trade action that creates economic links between the foreign investor and the host country. , this boosts the economy where investment will be made with the arrival of capital, generates more sources of work, encourages the transfer of new technologies and boosts national exports. Through the methodological implementation of a logical framework and the development of focus groups, information was collected to determine if FDI is a mechanism to reduce high unemployment indicators, fight against poverty and its social effects. Among the results, the lack of actions and conditions to encourage FDI stands out. Likewise, in the focus groups it was learned that political and social problems negatively affect FDI because they increase country risk and generate distrust in those who invest, as well as the lack of legal stability in tax issues; which creates distrust, another problem is the bureaucratic process to create and legalize companies in Ecuador. Finally, public policy recommendations or strategies were provided aimed at promoting FDI in Ecuador to improve the quality of life of citizens.